Pregled bakterijskih spolno prenosljivih bolezni (gonoreja, sifilis, klamidijska okužba) - Razpotnik, Saša (Placebo, 2025)
Syphilis, gonorrhoea, and chlamydia are key representatives of bacterial sexually transmitted diseases and the treatment of such diseases is becoming more and more challenging due to the emergence of antimicrobial resistance to established therapies. The consequences of inefficient treatment can be extremely debilitating to the affected (the development of neurosyphilis, cardiosyphilis, dementia, infertility, ectopical pregnancy), and can be harmful to congenitally infected infants (underdeveloped immune system, greater risk of complications, blindness due to conjunctival infection). Due to the potentially severe nature of the infections it is crucial that we establish a good understanding of their pathophysiology, which can enable further research, discovery and development of effective and innovative therapies, that exceed the established antibiotic treatments.
Keywords: antibiotic treatment; chlamydia; gonoreja; gonorrhoea; klamidijska okužba; nove terapije; novel therapies; pathophysiology of sexually transmitted bacterial infections; patofiziologija spolno prenosljivih bakterijskih okužb; sexually transmitted bacterial infections; sifilis; Spolne bolezni; spolno prenosljive bakterijske bolezni; syphilis; Zdravljenje; zdravljenje z antibiotiki